Anmeldelser - * (Økonomi & Politik, 2026)
Bogen tager udgangspunkt i spørgsmålet: »Should national EU policy be formulated in a foreign policy way, essentially, so that 'democratic luxury is sacrificed and political parties, government departments, interest organizations, and perhaps even the press restrain themselves in the name of the 'national interest'? Or should each be allowed to pursue their own parocichial interest?<< (s. ix)